A Histochemical Study of Normal and Denervated Red and White Muscles of the Rat - Nachmias, Vivianne T. (The Rockefeller University Press, 1958)
The distribution and characterization of the fibers of normal and denervated red and white muscles of the albino rat are reported in this study. Histochemical procedures for succinic dehydrogenase, lipides, adenosinetriphosphatase, esterase, and glycogen were utilized to differentiate muscle fibers, and these methods facilitated the study of the distribution of fiber types within whole muscle. Muscle fibers of the granular type (dark or red fibers) can be clearly distinguished from those with clearer sarcoplasm (light or white fibers) by methods for demonstrating succinic dehydrogenase, lipides, and esterase. The method for adenosine-triphosphatase reveals differences only under the special conditions described in the text. Additional fiber types are described in the cat's diaphragm and in the extrinsic ocular muscles of the rat. Succinic dehydrogenase and adenosinetriphosphatase activities of the soleus and biceps femoris were studied 14 days after denervation of these muscles. The histochemical findings are discussed principally in the light of current biochemical knowledge of these enzymes.